SIMULASI DEBIT DENGAN HYDROCAD BERDASARKAN HUJAN BULANAN DI DAS ALANG - Berklyson Tarigan; Rintis Hadiani; Suyanto Suyanto (Matriks Teknik Sipil, 2014)
Rainfall correlate with the characteristics of the DAS. Streamflow for a rainy directly correlate with the duration and intensity of rain. Theresearch is (1) to know the value of discharge parameters based of mounly rainfall in DAS Alang with HydroCAD application, (2) to knowsthe value of discharge from HydroCAD simulation to observation data, (3) to know the value correlation of discharge from HydroCADsimulation with observation data usingthe character of the DAS Alang.This research is descriptive quantitative research, where data used are secondary data. The secondary data from BTKPDAS instance. The researchphase implemented with collec dayly railfall of DAS Alang. The discharge of DAS Alang from 2002 - 2012. The results rainfall areas usingpolygon thieseen method. The rainfall areas insert to the application and then discharge simulation test. From HydroCAD application willproduce discharge simulation of DAS Alang, the produce of discharge simulation will be correlation with discharge from observation data ifcoefficiend's correlation R 0,8 until 1,0 showed a good correlation, if coefficient's correlation more than 0,4 less than 0,8 indicate the goodcorrelation, the coefficient between 0,2 until 0,4 showed not good correlation, if less than 0,2 can be ignored.The result of research to show that Curve Number CN and Time Concentration TC very influential in discharge simulation with HydroCADAplication . the less accurate of discharge observation data so the correlation value and the result discharge correlation and observation data usingTime Concentration method who different between Ponce method, Rasional method, SCS method. Using TC Ponce method to result the correlationvalue 0,8 until 1,0 in 2004,2006,2009,2011,2012, Using TC Rasional method to result the correlation value 0,8 until 1,0 in2004,2006,2011,2012, Using TC SCS method to result the correlation value 0,8 until 1,0 in 2004,2006,2009,2011,2012, it can beconciuded the TC Ponce method and TC SCS method have gred similarity of correlation coefficient. Can be applicatied in DAS Alang